Overcoat material for inkjet printing
The overcoat material for inkjet printing, using an AB block copolymer with UV-absorbing groups, addresses the insufficient light resistance and adhesion issues of conventional inks, creating a durable protective film with improved abrasion and chemical resistance.
Patent Information
- Application Number
- JP2021164690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-10-06
AI Technical Summary
Conventional inkjet inks used for outdoor applications lack sufficient light resistance and durability, particularly when exposed to intense sunlight, and do not provide adequate adhesion to printing substrates.
An overcoat material for inkjet printing containing an aqueous medium, surfactant, binder component, and specific alkali components, comprising an AB block copolymer with defined molecular weight and ultraviolet absorbing groups, forming emulsion particles for improved abrasion, chemical, and scratch resistance.
Enhances the light resistance and durability of printed materials by forming a protective film with excellent adhesion to the substrate, providing abrasion resistance, chemical resistance, and scratch resistance.
Smart Images

Figure 0007609752000001 
Figure 0007609752000002 
Figure 0007609752000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an overcoat material for ink jet printing. [Background technology]
[0002] In recent years, various printed materials, not only for business use or home use, have been produced by inkjet printing. For example, many outdoor advertisements, facility signs, displays, POP advertisements, and traffic advertisements, which are used as signs and displays in industrial applications, are produced by printing on large-sized printing substrates using inkjet recording devices. In addition, solvent-based inks are often used when producing signs and displays.
[0003] Printed matter such as signs and displays for outdoor use produced using inkjet inks is exposed to sunlight, including ultraviolet light, and is therefore prone to deterioration and fading. For this reason, in order to suppress deterioration due to ultraviolet light, inks containing pigments, which are crystalline particles with good light resistance, as coloring materials are used instead of dyes, which have poor light resistance.
[0004] However, since pigments are blended into inkjet printing inks in the form of small particles, their durability against ultraviolet rays is easily reduced. In addition, since it is necessary to improve the clarity and color development of an image while adjusting the hue, etc., it may be necessary to use pigments with relatively low lightfastness. For this reason, inkjet inks blended with ultraviolet absorbents have been proposed to improve the lightfastness of printed matter such as images (Patent Documents 1 and 2). In addition, inkjet inks using polymers containing monomers with ultraviolet absorbing groups as a pigment dispersant have been proposed (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-199808 [Patent Document 2] JP 2003-276323 A [Patent Document 3] JP 2000-7967 A Summary of the Invention [Problem to be solved by the invention]
[0006] By using the inks proposed in Patent Documents 1 to 3, it is possible to improve the lightfastness of the resulting printed matter. However, when printed matter for outdoor use is exposed for a long period of time to direct sunlight, which has become more intense due to the effects of global warming in recent years, the lightfastness of the printed matter produced using conventional inks is not necessarily sufficient. In addition, in recent years, there have been increasing opportunities to directly record on the outer surfaces of automobiles, aircraft, etc. to achieve effects such as designs and advertisements. However, the lightfastness of printed matter directly recorded on the outer surfaces of automobiles, etc. using conventional inks is insufficient, and there is room for improvement.
[0007] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide an overcoat material for inkjet printing that can improve the light fastness of printed matter, has excellent adhesion to a substrate to be printed, and is capable of forming a printing film that has excellent durability, such as abrasion resistance, chemical resistance, impact resistance, and scratch resistance. [Means for solving the problem]
[0008] That is, according to the present invention, there is provided an overcoat material as described below. [1] An overcoat material for inkjet printing, comprising an aqueous medium containing water and a water-soluble organic solvent, a surfactant, a binder component, and a first alkali component, wherein the binder component is a polymer (i) that satisfies the following requirements (1-1) to (1-5): (1-1) The content of structural units derived from methacrylic acid monomers is 90 mass % or more. (1-2) An AB block copolymer containing a polymer block A and a polymer block B, having a number average molecular weight of 10,000 to 50,000 and a molecular weight distribution of 1.2 to 1.8. (1-3) The polymer block A has a content of constituent units derived from an ultraviolet absorbing group-containing methacrylic acid monomer having an ultraviolet absorbing group having a benzotriazole skeleton or a triazine skeleton of 10 to 80% by mass, a content of constituent units derived from a methacrylic acid monomer other than the ultraviolet absorbing group-containing methacrylic acid monomer of 20 to 90% by mass, a number average molecular weight of 5,000 to 30,000, and a molecular weight distribution of 1.1 to 1.6. (1-4) The polymer block B has a content of constituent units derived from methacrylic acid of 10 to 50% by mass, and a content of constituent units derived from a methacrylic acid-based monomer other than methacrylic acid of 50 to 90% by mass. (1-5) The carboxyl group derived from the methacrylic acid is neutralized by the first alkaline component and self-emulsifies in the aqueous medium, forming emulsion particles having a number average particle size of 30 to 300 nm. [2] The overcoat material according to [1], wherein the first alkaline component is at least one selected from the group consisting of ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol. [3] The overcoat material according to [1] or [2] above, further comprising a polymer (ii) that satisfies the following requirements (2-1) and (2-2): (2-1) At least one carboxyl group-containing polymer selected from the group consisting of polyethylene, polypropylene, poly-α-olefin, and copolymers thereof is neutralized with a second alkaline component and self-emulsified in the aqueous medium to form emulsion particles having a number average particle size of 30 to 300 nm. (2-2) The acid value of the polymer having a carboxy group is 10 to 150 mgKOH / g. [4] The overcoat material according to [3], wherein the second alkaline component is at least one selected from the group consisting of ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol. [5] The ultraviolet absorbing group-containing methacrylic acid monomer is selected from the group consisting of 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole, 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-(2-ethylhexyloxy)-2-propyl methacryloyloxyethyl carbamate, 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl) The overcoat material according to any one of the above [1] to [4], which is at least one member selected from the group consisting of 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-dodecyloxy-2-propyl methacryloyloxyethyl carbamate, and 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-tridecyloxy-2-propyl methacryloyloxyethyl carbamate. [6] The overcoat material according to any one of [1] to [5], wherein the polymer (i) further contains 1 to 10 mass % of a structural unit derived from benzophenone methacrylate. Effect of the Invention
[0009] According to the present invention, it is possible to provide an overcoat material for inkjet printing that can improve the light fastness of printed matter, has excellent adhesion to a substrate to be printed, and is capable of forming a printed film that has excellent durability in terms of abrasion resistance, chemical resistance, impact resistance, scratch resistance, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Overcoat material> Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The overcoat material of the present invention is an overcoat material for inkjet printing, and contains an aqueous medium, a surfactant, a binder component, and a first alkaline component. The aqueous medium contains water and a water-soluble organic solvent. The binder component is an AB block copolymer (polymer (i)) that satisfies certain requirements. Hereinafter, the overcoat material of the present invention will be described in detail.
[0011] (aqueous medium) The aqueous medium contains water and a water-soluble organic solvent. The water-soluble organic solvent is a component for improving the moisture retention and drying property, and is also a component for adjusting the surface tension and viscosity. As the water-soluble organic solvent, those that are completely miscible with water are particularly preferable. However, those with a water solubility of about 20 g / 100 g at 25°C may also be used.
[0012] Examples of the water-soluble organic solvent include glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and dipropylene glycol; ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monobutyl ether, dipropylene glycol monomethyl ether, triethylene glycol monobutyl ether, and tripropylene glycol monopropyl ether. Examples of the alkyl group include glycol ethers such as ethylene glycol monomethyl ether, tetraethylene glycol monobutyl ether, and tetraethylene glycol dimethyl ether; alcohols such as ethanol, isopropanol, 3-butanol, 1,3-propanediol, glycerin, 1,6-hexanediol, and 3-methoxy-3-methyl-1-butanol; and 3-methyloxazolidinone, 2-pyrrolidone, 1-methyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, γ-butyrolactone, γ-butyrolactam, and dimethyl sulfoxide.
[0013] The content of the water-soluble organic solvent in the overcoat material is preferably 5 to 50% by mass, and more preferably 10 to 40% by mass. If the content of the water-soluble organic solvent is less than 5%, the ink tends to dry out in the nozzle of the recording head for inkjet printing, and ejection may become somewhat difficult. On the other hand, if the content of the water-soluble organic solvent is more than 50% by mass, the viscosity may become somewhat high, resulting in deterioration of printing characteristics, or the drying property of the printed matter may become somewhat poor.
[0014] (Surfactant) By including a surfactant in the overcoat material, the surface tension of the overcoat material can be adjusted to an appropriate range. By adjusting the surface tension to an appropriate range, the wettability of the overcoat material to the substrate can be improved, and droplets of the overcoat material ejected from an inkjet recording head can spread appropriately. The surface tension of the overcoat material at 25° C. is preferably 15 to 45 mN / m, and more preferably 20 to 40 mN / m.
[0015] Examples of the surfactant include silicone-based, acetylene glycol-based, fluorine-based, alkylene oxide-based, and hydrocarbon-based surfactants. Among them, fluorine-based surfactants and silicone-based surfactants are preferred. The content of the surfactant in the overcoat material is preferably 0.01 to 3 mass%, and more preferably 0.05 to 1 mass%. By setting the content of the surfactant within the above range, foaming of the overcoat material can be suppressed while being repelled by the surface of the non-printed material.
[0016] (Binder component) The binder component is a polymer (i) that satisfies the following requirements (1-1) to (1-5). (1-1) The content of structural units derived from methacrylic acid monomers is 90 mass % or more. (1-2) An AB block copolymer containing a polymer block A and a polymer block B, having a number average molecular weight of 10,000 to 50,000 and a molecular weight distribution of 1.2 to 1.8. (1-3) Polymer block A has a content of constituent units derived from an ultraviolet absorbing group-containing methacrylic acid monomer having an ultraviolet absorbing group having a benzotriazole skeleton or a triazine skeleton of 10 to 80 mass %, a content of constituent units derived from a methacrylic acid monomer other than an ultraviolet absorbing group-containing methacrylic acid monomer of 20 to 90 mass %, a number average molecular weight of 5,000 to 30,000, and a molecular weight distribution of 1.1 to 1.6. (1-4) Polymer block B has a content of constitutional units derived from methacrylic acid of 10 to 50 mass %, and a content of constitutional units derived from methacrylic acid-based monomers other than methacrylic acid of 50 to 90 mass %. (1-5) The carboxyl group derived from the methacrylic acid is neutralized by the first alkaline component and self-emulsifies in the aqueous medium, forming emulsion particles having a number average particle size of 30 to 300 nm.
[0017] The polymer (i) is a polymer containing 90% by mass or more of a constituent unit derived from (1-1) a methacrylic acid monomer, and is preferably a polymer substantially composed of only a constituent unit derived from a methacrylic acid monomer. In this specification, "methacrylic acid monomer" includes "methacrylic acid" and "methacrylic acid ester". By using a methacrylic acid monomer, the glass transition temperature (Tg) of the polymer (i) can be arbitrarily controlled, and the hydrolysis resistance in an alkaline aqueous solution can be improved. In addition, the structure of the AB block copolymer can be easily controlled, and the manufacturing conditions are also mild, which is preferable.
[0018] Polymer (i) is an AB block copolymer (1-2) containing polymer block A and polymer block B, having a number average molecular weight of 10,000 to 50,000 and a molecular weight distribution of 1.2 to 1.8. Polymer block A (hereinafter also simply referred to as "A chain") is a polymer block having an ultraviolet absorbing group. Polymer block B (hereinafter also simply referred to as "B chain") is a polymer block having a carboxy group, which is neutralized with a first alkali and can be dissolved in water.
[0019] The number average molecular weight (Mn) of the polymer (i) which is an AB block copolymer is 10,000 to 50,000, preferably 20,000 to 30,000. By setting the number average molecular weight (Mn) of the polymer (i) within the above range, a printing film (overcoat layer) excellent in abrasion resistance and adhesion to a printed substrate can be formed. If the number average molecular weight of the polymer (i) is less than 10,000, the physical properties of the printing film formed cannot be sufficiently improved. On the other hand, it takes an excessive amount of time to produce a polymer (i) having a number average molecular weight (Mn) of more than 50,000, and the particle size of the emulsion particles formed may become excessively large. The molecular weights of the polymers in this specification (number average molecular weight (Mn) and weight average molecular weight (Mw)) are values calculated in terms of polystyrene measured by gel permeation chromatography (GPC).
[0020] The molecular weight distribution (PDI) of polymer (i) (weight average molecular weight (Mw) / number average molecular weight (Mn)) is 1.1 to 1.8, and preferably 1.5 or less. If the PDI of polymer (i) exceeds 1.8, the polymer will contain a wide range of molecular weights, from small to large, making it difficult to form a printing film that is excellent in abrasion resistance and adhesion to the printed substrate.
[0021] (1-3) The polymer block A (A chain) has a content of 10 to 80% by mass of constitutional units derived from an ultraviolet absorbing group-containing methacrylic acid monomer having an ultraviolet absorbing group with a benzotriazole skeleton or triazine skeleton, a content of constitutional units derived from a methacrylic acid monomer other than an ultraviolet absorbing group-containing methacrylic acid monomer, a number average molecular weight of 5,000 to 30,000, and a molecular weight distribution of 1.1 to 1.6. The A chain is an ultraviolet absorbing polymer block capable of forming a durable water-insoluble coating. By using an overcoat material containing this AB block copolymer having an A chain as a binder component, it is possible to improve adhesion and abrasion resistance, increase the light resistance of printed matter, suppress fading of images, and maintain the color development, clarity, saturation, and hue of the image for a long period of time.
[0022] Examples of the ultraviolet absorbing group having a benzotriazole skeleton include a monovalent residue obtained by removing one hydrogen atom from a group having a structure represented by the following general formula (1). Examples of the ultraviolet absorbing group-containing methacrylic acid monomer having such an ultraviolet absorbing group include a compound in which a methacryloyl group is bonded directly or via another bond (such as an ester bond or an amide bond) to any position in the structure represented by general formula (1).
[0023] TIFF0007609752000001.tif40170
[0024] In the general formula (1), R and R' are each independently any one of a hydrogen atom, a halogen atom, an alkyl group, an alkenyl group, an allyl group, an alkoxy group, an ester group, and an oxycarbonyl group.
[0025] Examples of ultraviolet absorbing groups having a triazine skeleton include monovalent residues obtained by removing one hydrogen atom from a group having a structure represented by the following general formula (2). Examples of ultraviolet absorbing group-containing methacrylic acid monomers having such ultraviolet absorbing groups include compounds in which a methacryloyl group is bonded directly or via another bond (such as an ester bond or an amide bond) to any position in the structure represented by general formula (2).
[0026] TIFF0007609752000002.tif53170
[0027] In the general formula (2), R1 to R5 are each independently any one of a hydrogen atom, a halogen atom, an alkyl group, an alkenyl group, an allyl group, an alkoxy group, an ester group, a hydroxyl group, and an oxycarbonyl group.
[0028] Examples of ultraviolet absorbing group-containing methacrylic acid monomers having an ultraviolet absorbing group with a benzotriazole skeleton include compounds obtained by reacting 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole or 2-(2,4-dihydroxyphenyl)-2H-benzotriazole with methacrylic acid or glycidyl methacrylate.
[0029] Examples of ultraviolet absorbing group-containing methacrylic acid monomers having an ultraviolet absorbing group with a triazine skeleton include compounds obtained by reacting 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine with methacrylic acid, glycidyl methacrylate, or the like; 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[2-hydroxy-3-(dodecyloxy)propoxy]phenol; 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[2-hydroxy-3-(dodecyloxy)propoxy]phenol; compounds obtained by reacting 2-[4-[4,6-bis([1,1'-biphenyl]-4-yl)-1,3,5-triazin-2-yl]-3-hydroxyphenoxy]-propionic acid with glycidyl methacrylate, etc., can be mentioned.
[0030] As the ultraviolet absorbing group-containing methacrylic acid monomer having an ultraviolet absorbing group with a benzotriazole skeleton, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (maximum absorption wavelength: 338.5 nm) is preferred.
[0031] Examples of ultraviolet absorbing group-containing methacrylic acid monomers having an ultraviolet absorbing group with a triazine skeleton include 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-(2-ethylhexyloxy)-2-propyl methacryloyloxyethyl carbamate (maximum absorption wavelength 336 nm), 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-(2-ethylhexyloxy)-2-propyl methacryloyloxyethyl carbamate (maximum absorption wavelength 336 nm), [3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-dodecyloxy-2-propyl methacryloyloxyethyl carbamate (maximum absorption wavelength 340 nm), 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-tridecyloxy-2-propyl methacryloyloxyethyl carbamate (maximum absorption wavelength 340 nm) are preferred.
[0032] In the polymer block A, the content of the constitutional unit derived from the ultraviolet absorbing group-containing methacrylic acid monomer is 10 to 80% by mass, preferably 20 to 70% by mass, and more preferably 30 to 50% by mass. If the content of the constitutional unit derived from the ultraviolet absorbing group-containing methacrylic acid monomer is less than 10% by mass, the effect of improving light resistance becomes insufficient. On the other hand, if the content of the constitutional unit derived from the ultraviolet absorbing group-containing methacrylic acid monomer exceeds 80% by mass, the polymerizability decreases, the molecular weight of the obtained polymer (i) does not increase, and the monomer that remains unpolymerized is easily introduced into the B chain. For this reason, the B chain is easily made water-insoluble, and the adhesion and abrasion resistance of the formed printing film are reduced.
[0033] In the A chain, the content of constitutional units derived from methacrylic acid monomers other than the ultraviolet absorbing group-containing methacrylic acid monomer (other methacrylic acid monomers) is 20 to 90 mass %. By including constitutional units derived from other monomers in the A chain, the properties of the printed film formed can be further improved and the molecular weight of the obtained polymer (i) can be adjusted. Other methacrylic acid monomers include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, t-butyl methacrylate, and hexyl methacrylate; methacrylic acid alicyclic alkyl esters such as cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, trimethylcyclohexyl methacrylate, isobornyl methacrylate, and dicyclopentanyl methacrylate; glycol methacrylic acid esters such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, butoxyethyl methacrylate, dicyclopentenyloxyethyl methacrylate, polyethylene glycol monomethacrylate, and polyethylene glycol monomethyl ether methacrylate; and amino group-containing methacrylates such as dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate.
[0034] The number average molecular weight (Mn) of the A chain is 5,000 to 30,000, preferably 10,000 to 25,000, and the PDI is 1.1 to 1.6. If the number average molecular weight (Mn) of the A chain is less than 5,000, it becomes difficult to form a printing film having excellent abrasion resistance and adhesion to the substrate to be printed. On the other hand, if the number average molecular weight (Mn) of the A chain exceeds 30,000, the particle size of the emulsion particles formed becomes too large, and the ejection property from the recording head of the inkjet method decreases.
[0035] (1-4) Polymer block B (B chain) has a content of constituent units derived from methacrylic acid of 10 to 50% by mass, and a content of constituent units derived from methacrylic acid-based monomers other than methacrylic acid of 50 to 90% by mass. The B chain is a polymer block having a carboxy group derived from methacrylic acid, which is neutralized with a first alkali and can be dissolved in water. The water-insoluble A chain forms particles, while the B chain dissolves in water, so that polymer (i), which is an AB block copolymer having these A chains and B chains, can form emulsion particles in an aqueous medium.
[0036] In the polymer block B, the content of the structural unit derived from methacrylic acid is 10 to 50% by mass, preferably 15 to 30% by mass. If the content of the structural unit derived from methacrylic acid is less than 10% by mass, the B chain may not dissolve in water, and the polymer (i) may not form emulsion particles. On the other hand, if the content of the structural unit derived from methacrylic acid is more than 50% by mass, the water resistance of the overcoat layer formed may decrease, and the viscosity of the overcoat material may increase.
[0037] In the B chain, the content of constituent units derived from methacrylic acid monomers other than methacrylic acid (other methacrylic acid monomers) is 50 to 90% by mass. Examples of the other methacrylic acid monomers include the same as the other methacrylic acid monomers used in the A chain.
[0038] The polymer (i) is self-emulsified in the aqueous medium as the carboxyl group derived from the (1-5) methacrylic acid is neutralized with the first alkali component, forming emulsion particles having a number average particle size of 30 to 300 nm.
[0039] Examples of the first alkaline component include ammonia; aliphatic primary to tertiary amines such as monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, and triethylamine; alcohol amines such as monoethanolamine, diethanolamine, triethanolamine, monopropanolamine, dipropanolamine, tripropanolamine, methylethanolamine, dimethylethanolamine, and 2-amino-2-methyl-1-propanol; heterocyclic amines such as piperidine, morpholine, and N-methylmorpholine; and alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide. Among these, ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol are preferred as the first alkaline component. These first alkaline components are easily volatilized at room temperature or under heating conditions. Therefore, when these first alkaline components are used, these first alkaline components are volatilized from the overcoat layer formed by drying, and the B chain becomes water-insoluble, so that the water resistance of the overcoat layer can be improved.
[0040] The number average particle diameter of the emulsion particles is 30 to 300 nm, preferably 50 to 150 nm. If the number average particle diameter of the emulsion particles is less than 30 nm, the viscosity of the overcoat material becomes too high, and the hydrophilicity of the printed film formed becomes too high. On the other hand, if the number average particle diameter of the emulsion particles is more than 300 nm, foreign matter, so-called "lumps," tends to form in the printed film formed. Furthermore, the nozzle of the recording head tends to be clogged, and the ejection property and filterability of the overcoat material may be reduced. The number average particle diameter of the emulsion particles in this specification is a physical property value measured and calculated using a dynamic light scattering type particle size distribution measuring device.
[0041] The polymer (i) (AB block copolymer) can be synthesized by a conventional method. Among them, polymerization methods having living properties such as living anionic polymerization, living cationic polymerization, and living radical polymerization are preferred, and living radical polymerization is particularly preferred from the viewpoints of conditions, materials, and equipment. Examples of living radical polymerization methods include atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer polymerization (RAFT), nitroxide method (NMP), organotellurium method (TERP), reversible transfer catalysis polymerization (RTCP), and reversible catalyst-mediated polymerization (RCMP). Among them, the RTCP and RCMP methods using an organic compound as a catalyst and an organic iodide as a polymerization initiator compound are preferred. These methods use relatively safe commercially available compounds, do not use heavy metals or special compounds, and are advantageous in terms of cost and purification. Furthermore, by making the growth terminal a tertiary iodine, a block structure with good accuracy can be easily formed using general equipment.
[0042] The polymerization may be either thermal polymerization or photopolymerization, and an azo-based radical generator, a peroxide-based radical generator, a photosensitizer, or the like may be added to the polymerization reaction system. The polymerization method may be any of solventless polymerization, solution polymerization, and emulsion polymerization, and among them, solution polymerization is preferred. By using the same water-soluble organic solvent as the water-soluble organic solvent in the aqueous medium used for the overcoat material as the solvent during solution polymerization, it is preferable because the overcoat material can be prepared using the obtained AB block copolymer solution as it is.
[0043] Either the A chain or the B chain may be polymerized first. However, if the B chain is polymerized first, methacrylic acid may remain in the polymerization reaction system. In this case, a structural unit derived from methacrylic acid may be introduced into the A chain that is polymerized thereafter. For this reason, it is preferable to polymerize the A chain first and then the B chain, in order to avoid the introduction of a structural unit derived from methacrylic acid into the A chain.
[0044] An overcoat material can be prepared by neutralizing, emulsifying, and dispersing the AB block copolymer obtained according to a conventional method. For example, an aqueous solution of a first alkaline component can be added while stirring a solution of the AB block copolymer obtained by solution polymerization, thereby neutralizing the carboxyl groups of the AB block copolymer and self-emulsifying it in an aqueous medium to form emulsion particles. In addition, the AB block copolymer extracted after polymerization by a method such as (i) drying, (ii) precipitating in a poor solvent, or (iii) neutralizing and dissolving in water, followed by adding an acid to precipitate, can be neutralized and emulsified and dispersed in an aqueous medium, and may be heated as necessary.
[0045] The content of the binder component in the overcoat material is preferably 1 to 20% by mass, and more preferably 3 to 10% by mass. If the content of the binder component is less than 1% by mass, it may be somewhat difficult to form a printing film (overcoat layer) of sufficient thickness. If the content of the binder component is more than 20% by mass, the viscosity of the overcoat material may become excessively high, which may decrease the ejection property or cause the formed printing film to become too thick.
[0046] By crosslinking the polymer (i) as the binder component to form a three-dimensional structure, the durability of the printed film formed can be improved, and the overcoat material can be more suitable for producing printed matter for outdoor use exposed to external factors such as wind and rain. Specifically, it is preferable that the polymer (i) further contains a structural unit derived from benzophenone methacrylate. The structural unit derived from benzophenone methacrylate has the property of being crosslinked by ultraviolet light. For this reason, when sunlight (ultraviolet light) hits an overcoat layer formed with an overcoat material containing the polymer (i) containing a structural unit derived from benzophenone methacrylate as a binder component, the structural unit derived from benzophenone methacrylate is intermolecularly crosslinked with other structural units, and the overcoat layer is hardened to improve durability.
[0047] The content of the structural unit derived from benzophenone methacrylate in the polymer (i) is preferably 1 to 10 mass %, more preferably 2 to 5 mass %. The structural unit derived from benzophenone methacrylate may be contained in at least one of the A chain and the B chain.
[0048] (Polymer (ii)) It is preferable that the overcoat material of the present invention further contains a polymer (ii) that satisfies the following requirements (2-1) and (2-2). (2-1) The carboxy group of at least one polymer having a carboxy group selected from the group consisting of polyethylene, polypropylene, poly-α-olefin, and copolymers thereof is neutralized with a second alkaline component and self-emulsified in the aqueous medium to form emulsion particles having a number average particle size of 30 to 300 nm. (2-2) The acid value of the polymer having a carboxy group is 10 to 150 mgKOH / g.
[0049] This polymer (ii) is a hydrophobic polymer and has a high affinity for plastic films such as polyolefin films, etc. Therefore, by including polymer (ii), the water repellency, oil repellency, and abrasion resistance of the formed printing film can be further improved.
[0050] Specific examples of polyethylene, polypropylene, polyα-olefin, and copolymers thereof include homopolymers and copolymers of α-olefins such as 1-butene, 1-hexene, 1-octene, and 1-octadecene. The polymer (ii) may have a branched structure or may be a block copolymer. Polymers such as polyethylene, polypropylene, polyα-olefin, and copolymers thereof may be oxidized; added with maleic anhydride or the like; pyrolyzed; or copolymerized with acrylic acid or methacrylic acid to obtain polymer (ii) having a carboxy group introduced therein.
[0051] The acid value of the polymer having a carboxy group is 10 to 150 mgKOH / g, preferably 20 to 100 mgKOH / g. If the acid value of the polymer having a carboxy group is less than 10 mgKOH / g, it may be difficult to emulsify sufficiently. On the other hand, if the acid value of the polymer having a carboxy group is more than 150 mgKOH / g, it may be difficult to emulsify or disperse the polymer, and the water resistance of the printed film formed may be slightly reduced.
[0052] The polymer (ii) may be a wax having a number average molecular weight of 10,000 or less, or may be a polymer having a number average molecular weight of tens of thousands or more. The melting point (or softening point) of the polymer (ii) is usually 0 to 180° C. The melting point of the polymer (ii) is preferably 120° C. or less, since it is more suitable for emulsification.
[0053] The number average particle size of the emulsion particles formed by the polymer (ii) is 30 to 300 nm, preferably 50 to 120 nm. If the number average particle size of the emulsion particles is less than 30 nm, the viscosity of the overcoat material may become excessively high. On the other hand, if the number average particle size of the emulsion particles is more than 300 nm, the overcoat material may easily clog the nozzles of the recording head, and the ejection property and filterability of the ink may be somewhat reduced.
[0054] The polymer (ii) is heated to melt, or heated and dissolved in a solvent such as toluene as necessary, and then an aqueous solution of the second alkaline component is added to neutralize the carboxyl group. When a solvent such as toluene is used, the solvent is distilled off. This makes it possible to obtain a polymer emulsion containing emulsion particles that are self-emulsified and dispersed in an aqueous medium. The second alkaline component may be the same as the first alkaline component described above. Among them, the second alkaline component is preferably ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol.
[0055] The content of polymer (ii) in the overcoat material is preferably 0.05 to 5 mass%, more preferably 0.1 to 1 mass%. If the content of polymer (ii) is less than 0.05 mass%, the effect may not be exhibited due to the small amount. On the other hand, if the content of polymer (ii) is more than 5 mass%, the characteristics of polymer (ii) tend to be significantly exhibited in the overcoat layer formed, and the desired effect of the overcoat material may not be exhibited.
[0056] (Other Ingredients) The overcoat material may further contain a preservative. Examples of the preservative include sodium benzoate, benzimidazole, thiabendazole, potassium sorbitanate, sodium sorbitanate, sodium dehydroacetate, thiazosulfamide, and pyridinethiol oxide. The content of the preservative in the overcoat material is preferably 0.05 to 2.0% by mass, and more preferably 0.1 to 1.0% by mass, based on the total mass of the overcoat material.
[0057] The overcoat material may further contain additives such as organic solvents other than the above-mentioned water-soluble organic solvents, dyes, leveling agents, surface tension adjusters, pH adjusters, UV absorbers, light stabilizers, antioxidants, dyes, fillers, waxes, thickeners, defoamers, anti-mold agents, antistatic agents, metal fine particles, and magnetic powders, as required.
[0058] (Manufacturing of overcoat materials) Water, a water-soluble organic solvent, a surfactant, a binder component, and an emulsion of polymer (ii) used as needed are mixed in a predetermined ratio and thoroughly mixed using a disperser or the like. Next, other additives used as needed are added, and an alkaline substance or the like is further added to adjust the pH. After that, the mixture is filtered through a filter or the like to remove coarse particles and dust, thereby producing the desired overcoat material.
[0059] It is preferable to adjust the viscosity of the overcoat material to an appropriate level so that it can be ejected from the nozzles of an inkjet recording head. The viscosity of the overcoat material at 25°C is preferably 2 to 10 mPa·s. The pH of the overcoat material at 25°C is preferably 7.0 to 10.0, and more preferably 7.5 to 9.5. If the pH of the overcoat material is less than 7.0, the binder component may be more likely to precipitate. On the other hand, if the pH of the overcoat material is more than 10.0, the recording head may be more likely to deteriorate due to its strong alkalinity.
[0060] <Use of overcoat material> By using an inkjet printer loaded with a cartridge filled with an overcoat material, and applying the overcoat material by the inkjet method on an image recorded (printed) by the inkjet recording method, a transparent overcoat layer, which is a printed film, can be formed. In addition, the overcoat layer formed protects the printed matter from ultraviolet rays and has excellent abrasion resistance, so that the durability of the printed matter can be improved. The printed matter may be a printed matter recorded with an inkjet ink using a dye, or a printed matter recorded with an inkjet ink using a pigment. An overcoat printed matter can be obtained by using an inkjet printer loaded with a cartridge filled with an overcoat material together with a cartridge filled with ink, and applying the overcoat material simultaneously with or after printing. In addition, the overcoat material may be applied on the printed matter by screen printing or slit coat printing.
[0061] Examples of substrates (printed substrates) constituting printed matter include paper, glossy paper, photo paper, inkjet paper, and plastic films such as polyolefin, polyester, polyamide, and polyvinyl halide. By applying an overcoat material onto these printed substrates, a transparent printing film can be formed. In addition, a transparent film coated with an overcoat material to form an overcoat layer can be used as an ultraviolet absorbing film. EXAMPLES
[0062] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.
[0063] <Production of polymer emulsion (1)> (Synthesis Example 1) Diethylene glycol monobutyl ether (BDG) 160 parts, propylene glycol monomethyl ether (MPG) 160 parts, iodine 1.2 parts, 2,2-azobis (4-methoxy-2,4-dimethylvaleronitrile) (trade name "V-70", Fujifilm Wako Pure Chemical Industries, Ltd.) (V-70) 4.4 parts, diphenylmethane (DPM) 0.1 parts, benzyl methacrylate (BzMA) 114.4 parts, 2- (2'-hydroxy-5'-methacryloxyethylphenyl) -2H-benzotriazole (RUVA-1) 64.7 parts, and 2-hydroxyethyl methacrylate (HEMA) 13.0 parts were placed in a reaction vessel. The mixture was stirred while bubbling nitrogen and heated to 45 ° C., and polymerized for 4.5 hours to synthesize polymer chain A (A chain). The solid content measured by sampling a portion of the reaction solution was 37.0%, and the polymerization conversion rate (yield) calculated based on the solid content was about 100%. The number average molecular weight (Mn) of the A chain measured by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a developing solvent was 10,000 in terms of polystyrene, and the polydispersity (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) was 1.30.
[0064] The obtained solution of A chain was cooled to 40°C, and then 1.9 parts of V-70, 18.5 parts of methacrylic acid (MAA), 65.1 parts of BzMA, and 33.6 parts of cyclohexyl methacrylate (CHMA) were added. Polymerization was carried out at 40°C for 4 hours to form polymer chain B (B chain), and a block copolymer was obtained. A part of the reaction solution was sampled and measured for solid content of 48.5%, and the polymerization conversion rate (yield) was about 100%. The Mn of the obtained block copolymer was 16,000 and the PDI was 1.42. The acid value (actual value) of the block copolymer measured by titration with an ethanolic 0.1 mol / L potassium hydroxide solution was 38.9 mg KOH / g.
[0065] The obtained block copolymer solution was neutralized by adding a mixture of 14.4 parts of 28% ammonia water (1.1 times the molar amount of methacrylic acid) and 625.6 parts of ion-exchanged water at room temperature to obtain polymer emulsion E-1. The solid content of polymer emulsion E-1 was 24.9%, and the pH (25°C) was 8.8. The number average particle size of the emulsion particles in polymer emulsion E-1, measured using a dynamic light scattering particle size distribution measuring device (particle size measuring device, product name "NICOMP 380ZLS-S", manufactured by International Business Co., Ltd.), was 50.3 nm.
[0066] (Synthesis Examples 2 to 5) Polymer emulsions E-2 to E-5 were obtained in the same manner as in Synthesis Example 1 described above, except that the formulations were as shown in Table 1. The properties of the obtained polymer emulsions E-2 to E-5 are shown in Table 1. The meanings of the abbreviations in Table 1 are as follows. EHMA: 2-Ethylhexyl methacrylate MMA: Methyl methacrylate ·BPMA: Benzophenone methacrylate ·DMAE: Dimethylaminoethanol ·AMP: 2-amino-2-methyl-1-propanol
[0067] TIFF0007609752000003.tif213170
[0068] <Synthesis of Monomers Containing UV-Absorbing Groups> (Synthesis Example 6) 48.8 parts of 3-methoxy-N,N-dimethylpropionamide (MDMPA), 58.3 parts of 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-[2-hydroxy-3-(2-ethylhexyloxy)propoxy]phenol (trade name "Tinuvin 405", manufactured by BASF), and 25 parts of 0.1% tin dilaurate solution in MDMPA were placed in a reaction vessel and heated to 80°C. 15.5 parts of 2-isocyanatoethyl methacrylate (trade name "Kalends MOI", manufactured by Showa Denko) were added dropwise over 1 hour, and the reaction was carried out at 80°C for 7 hours. After the reaction was completed, a portion of the reaction solution was sampled and the IR absorption was measured using an infrared spectrophotometer. As a result, the IR absorption at 2,260 cm -1 The absorption near 3,340cm (isocyanate group) disappears. -1 It was confirmed that absorption near the -NH- of the urethane bond was produced. The non-volatile content was 50.1%. This resulted in the production of a UV-absorbing group-containing monomer, 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-(2-ethylhexyloxy)-2-propyl methacryloyloxyethyl carbamate (RUVA-2, maximum absorption wavelength 336 nm).
[0069] <Production of polymer emulsion (2)> (Synthesis Example 7) BDG 120.1 parts, MDMPA 97.9 parts, 2-cyano-2-iodo-propane 1.56 parts, V-70 2.4 parts, BzMA 140.8 parts, RUVA-2 MDMPA solution 44.3 parts, and N-iodosuccinimide 0.2 parts were placed in a reaction vessel. The mixture was stirred while bubbling nitrogen and heated to 45°C, and polymerized for 4.5 hours to synthesize polymer chain A (A chain). A part of the reaction solution was sampled and measured for solid content of 40.9%, and the polymerization conversion rate was about 100%. The Mn of A chain was 15,000 and the PDI was 1.21.
[0070] The obtained solution of A chain was cooled to 40°C, and then 1.9 parts of V-70, 12.9 parts of MAA, 33.6 parts of CHMA, and 30.0 parts of methyl methacrylate (MMA) were added. Polymerization was carried out at 40°C for 4 hours to form polymer chain B (B chain), and a block copolymer was obtained. A part of the reaction solution was sampled and measured for solid content of 48.5%, and the polymerization conversion rate was about 100%. The obtained block copolymer had Mn of 18,300, PDI of 1.31, and acid value of 35.0 mgKOH / g.
[0071] The obtained block copolymer solution was neutralized by adding a mixture of 10 parts of 28% ammonia water and 470 parts of ion-exchanged water at room temperature to obtain polymer emulsion E-6. The solid content of polymer emulsion E-6 was 25.3% and the pH was 8.3. The number average particle size of the emulsion particles in polymer emulsion E-6 was 107.6 nm.
[0072] <Production of polymer emulsion (3)> (Comparative Synthesis Example 1) 252.8 parts of BDG, 0.4 parts of iodine, 1.4 parts of V-70, 0.1 parts of DPM, 80.4 parts of BzMA, 90.5 parts of EHMA, and 15.2 parts of HEMA were placed in a reaction vessel. The mixture was stirred while bubbling nitrogen and heated to 45°C, and polymerized for 4.5 hours to synthesize A-chain. The polymerization conversion was about 100%, and the Mn of A-chain was 26,000 and the PDI was 1.38.
[0073] The obtained solution of A chain was cooled to 40°C, and then 1.9 parts of V-70, 11.8 parts of MAA, 24.1 parts of BzMA, and 27.1 parts of EHMA were added. Polymerization was carried out at 40°C for 4 hours to form B chain, and a block copolymer was obtained. A part of the reaction solution was sampled and measured for solid content of 48.9%, and the polymerization conversion rate was about 100%. The obtained block copolymer had Mn of 29,000, PDI of 1.51, and acid value of 30.8 mgKOH / g.
[0074] The obtained block copolymer solution was diluted by adding 56.2 parts of BDG. At room temperature, a mixture of 9.1 parts of 28% ammonia water and 383.8 parts of ion-exchanged water was added to neutralize, and polymer emulsion H-1 was obtained. The solid content of polymer emulsion H-1 was 25.4%, and the number average particle size of the emulsion particles was 86.0 nm.
[0075] (Comparative Synthesis Example 2) 300 parts of ion-exchanged water was placed in a reaction vessel and heated to 75°C, after which 1 part of sodium persulfate was added. In addition, 100 parts of styrene, 50 parts of butyl acrylate, 50 parts of RUVA-1, and 6 parts of a reactive surfactant (trade name "Aqualon KH-10", Daiichi Kogyo Yakuhin Co., Ltd.) were placed in a separate vessel and mixed at 50°C to prepare a homogeneous monomer mixture. The monomer mixture prepared using a dropping funnel was dropped into the reaction vessel over 2 hours, and then reacted at 75°C for 4 hours to obtain a slightly transparent bluish-white polymer emulsion H-2. The solid content of polymer emulsion H-2 was 40.2%, the viscosity was 39 mPa·s, and the number average particle size of the emulsion particles was 132 nm.
[0076] <Production of Polymer Emulsion (Polymer II)> (Synthesis Example 8) 100 parts of oxidized polyethylene wax (melting point 150°C, acid value 20mgKOH / g) and 100 parts of toluene were placed in a reaction vessel and heated to 90°C to homogenize. While vigorously stirring the contents, a mixture of 3.3 parts of dimethylaminoethanol and 368.1 parts of ion-exchanged water was gradually added so as not to lower the temperature, and emulsified by phase inversion. Toluene and water were distilled off by heating, and the heating was continued until toluene was no longer detected by gas chromatography. Ion-exchanged water was added to adjust the solid content to 20%, and a yellowish translucent polymer emulsion O-1 was obtained. The pH of the obtained polymer emulsion O-1 was 8.8, and the number average particle size of the emulsion particles was 86.3 nm.
[0077] <Manufacturing of overcoat materials> (Examples 1 to 9, Comparative Examples 1 to 3) The components (unit: parts) shown in the upper part of Tables 2 and 3 were mixed and thoroughly homogenized by stirring for 30 minutes using a disperser. After that, the mixture was filtered through a 5 μm filter to remove coarse particles and dust, and overcoat materials OV-1 to 9 and overcoat materials HOV-1 and 2 were obtained. As shown in Table 3, overcoat material HOV-3 was obtained using polymer emulsion H-1 obtained in Comparative Synthesis Example 1 and a non-polymerized water-soluble low molecular weight ultraviolet absorber (trade name "Tinuvin 1130" (manufactured by BASF). The amount of each polymer emulsion in Tables 2 and 3 means the pure content (amount) of the polymer contained in each polymer emulsion. In addition, in Tables 2 and 3, "DMDG" is diethylene glycol dimethyl ether. As the "surfactant", the trade name "Silface SAG-503A" (manufactured by Shin-Etsu Chemical Co., Ltd.) was used.
[0078] TIFF0007609752000004.tif127170
[0079] TIFF0007609752000005.tif130170
[0080] <Manufacture of inkjet inks and printed materials> (Production Example 1) 675 parts of ion-exchanged water, 50 parts of BDG, 140 parts of pigment dispersant, and 150 parts of CI Pigment Blue 15:3 (PB15:3, manufactured by Dainichiseika Chemicals Co., Ltd.) were mixed, and thoroughly stirred and mixed using a dissolver to obtain a mixture. As the pigment dispersant, a copolymer (Mn20,000, PDI2.2) of styrene / methyl methacrylate / 2-hydroxyethyl methacrylate / 2-hydroxyethyl methacrylate / methacrylic acid = 20 / 10 / 10 / 20 / 10 / 10 was neutralized with ammonia and dissolved in propylene glycol monopropyl ether / dipropylene glycol monomethyl ether / water = 1 / 1 / 2 (mass ratio) (solid content 35%) was used. The mixture obtained was placed in a paint shaker with a filling rate of 40 volume% of the dispersion media using zirconia beads (diameter 1 mm) as the dispersion medium, and dispersed for 120 minutes to obtain a dispersion liquid. The obtained dispersion was centrifuged (7,500 rpm, 20 minutes) and then filtered through a 10 μm membrane filter to remove coarse particles. Ion-exchanged water was added to adjust the concentration, and a blue pigment dispersion with a pigment concentration of 14% was obtained.
[0081] 37.1 parts of the obtained pigment dispersion, 5 parts of pyrrolidone, 10 parts of triethylene glycol monobutyl ether, 30 parts of a 1% aqueous solution of a fluorine-based surfactant (trade name "Surflon S-211", manufactured by Asahi Glass Co., Ltd.), 0.2 parts of a preservative (trade name "Proxel GXL", manufactured by Avecia Co., Ltd.), and 17.7 parts of ion-exchanged water were mixed by stirring using a disper. The mixture was then filtered through a 1 μm membrane filter and a 0.5 μm membrane filter to obtain a blue ink.
[0082] The obtained blue ink was filled into a cartridge and attached to an inkjet printer equipped with a plate heater (product name "MMP825H", manufactured by Mastermind). A solid image was recorded on a substrate to be printed (polyethylene terephthalate (PET) film, manufactured by Futamura Chemical Co., Ltd., 60 μm) by the inkjet method to obtain print-1. Specifically, the substrate to be printed was heated using a plate heater so that the surface temperature reached 50° C., and then the blue ink was applied and printed.
[0083] (Production Example 2) Except for using CI Pigment Red 122 (PR122, Dainichiseika Color & Chemicals Mfg. Co., Ltd.) instead of PB15:3, a red ink was obtained in the same manner as in Production Example 1. Furthermore, except for using red ink instead of blue ink, a printed matter-2 was obtained in the same manner as in Production Example 1.
[0084] (Production Examples 3 and 4) Yellow ink-1 and yellow ink-2 were obtained in the same manner as in Production Example 1 except that CI Pigment Yellow 74 (PY74, Dainichiseika Color & Chemicals Mfg. Co., Ltd.) and CI Pigment Yellow 155 (PY155, Clariant Japan K.K.) were used instead of PB15:3. Furthermore, printed matter-3 and printed matter-4 were obtained in the same manner as in Production Example 1 except that yellow ink-1 and yellow ink-2 were used instead of blue ink.
[0085] <Production and evaluation of overcoat prints> (Examples 10 to 21 and Comparative Examples 4 to 6) The types of overcoat materials shown in Table 4 were filled into cartridges and installed in an inkjet printer. The overcoat materials were then applied to the entire surfaces of the types of printed matter shown in Table 4 by the inkjet method in the same manner as in Production Example 1 described above, to obtain overcoat printed matter OV printed matter-1 to 13 and overcoat printed matter HOV printed matter-1 to 3.
[0086] (Discharge stability) The state of ejection of the overcoat material from the recording head of the inkjet printer was visually observed, and the ejection stability of the overcoat material was evaluated according to the following evaluation criteria. The results are shown in Table 4. Of the evaluation criteria shown below, "○" was considered to be acceptable. ◯: Discharge was possible without any problems, and a good overcoat layer was printed. △: Scattering of minute droplets was observed. ×: Droplets were scattered during ejection, causing image disturbance.
[0087] (Adhesion) The adhesion of the overcoat layer to the printed substrate was evaluated by a cellophane tape peeling test. Specifically, the printed matter was thoroughly dried using a dryer, and then cellophane tape (product name "Cellotape (registered trademark), manufactured by Nichiban Co., Ltd.") was thoroughly pressed against the overcoat layer and then peeled off. The degree of peeling of the overcoat layer after peeling was visually observed, and the adhesion was evaluated according to the evaluation criteria shown below. The results are shown in Table 4. Of the evaluation criteria shown below, "◎" and "○" were considered to be acceptable. ⊚: The overcoat layer did not peel off at all. A: The overcoat layer was slightly peeled off. Δ: The area of the peeled overcoat layer was smaller than the area of the overcoat layer that remained unpeeled. ×: The area of the peeled overcoat layer was larger than the area of the overcoat layer that remained unpeeled.
[0088] (Abrasion resistance) Using a Gakushin-type friction fastness tester (product name "RT-300", manufactured by Daiei Kagaku Co., Ltd.), the surface of the overcoat layer of the obtained print was subjected to (1) dry rubbing by 20 reciprocations with a white cloth weighing 500 g; and (2) wet rubbing by 20 reciprocations with a white cloth moistened with water weighing 500 g. The condition of the overcoat layer after rubbing was visually observed, and the friction resistance was evaluated according to the evaluation criteria shown below. The results are shown in Table 4. Of the evaluation criteria shown below, "◎" and "○" were considered to be acceptable. ⊚: The overcoat layer did not peel off at all. A: The overcoat layer was slightly peeled off. Δ: The area of the peeled overcoat layer was smaller than the area of the overcoat layer that remained unpeeled. ×: The area of the peeled overcoat layer was larger than the area of the overcoat layer that remained unpeeled.
[0089] (Lightfastness) Eye Super UV Tester (product name "SUV-161W", metal halide lamp, manufactured by Iwasaki Electric Co., Ltd., lamp illuminance 50mW / cm 2A lightfastness test was conducted in which the surface of the printed matter was irradiated with ultraviolet light for 100 hours using a 300-deg. C (63°C) tester. The color difference (ΔE) before and after ultraviolet light exposure was measured and calculated, and the lightfastness was evaluated according to the evaluation criteria shown below. The results are shown in Table 4. Of the evaluation criteria shown below, "○" and "△" were considered to be acceptable. ◯: ΔE was less than 1.0. △: ΔE was 1.0 or more and less than 3.0. ×: ΔE was 3.0 or more.
[0090] TIFF0007609752000006.tif106170
[0091] A drop of methyl ethyl ketone (MEK) was dropped onto the overcoat layer of OV printed matter-2 (Example 11) and OV printed matter-7 (Example 16) after the lightfastness test. As a result, the overcoat layer of OV printed matter-2 dissolved, but the overcoat layer of OV printed matter-7 did not dissolve, and only wrinkled slightly. The overcoat material OV-7 that formed the overcoat layer of OV printed matter-7 contains a binder component (polymer emulsion E-5) having a structural unit derived from benzophenone methacrylate. For this reason, it is considered that the benzophenone group in the binder component reacted with ultraviolet light to crosslink, and the formed overcoat layer further hardened. [Industrial Applicability]
[0092] The overcoat material of the present invention is useful as a protective film for protecting printed matter, for example, outdoor advertising materials, automobiles, aircraft, exterior walls, etc. In addition, by coating a transparent film, etc., it is also possible to produce a transparent ultraviolet absorbing film, and it is expected to be applied to films for protecting contents, etc.
Claims
1. An overcoat material for inkjet printing, comprising an aqueous medium containing water and a water-soluble organic solvent, a surfactant, a binder component, and a first alkali component, The overcoat material, wherein the binder component is a polymer (i) that satisfies the following requirements (1-1) to (1-5): (1-1) The content of structural units derived from methacrylic acid-based monomers is 90% by mass or more. (1-2) An AB block copolymer containing a polymer block A and a polymer block B, having a number average molecular weight of 10,000 to 50,000 and a molecular weight distribution of 1.2 to 1.
8. (1-3) The polymer block A has a content of structural units derived from an ultraviolet absorbing group-containing methacrylic acid monomer having an ultraviolet absorbing group having a benzotriazole skeleton or a triazine skeleton of 10 to 80% by mass, a content of structural units derived from a methacrylic acid monomer other than the ultraviolet absorbing group-containing methacrylic acid monomer of 20 to 90% by mass, a number average molecular weight of 5,000 to 30,000, and a molecular weight distribution of 1.1 to 1.
6. (1-4) The polymer block B has a content of constituent units derived from methacrylic acid of 10 to 50% by mass, and a content of constituent units derived from a methacrylic acid-based monomer other than methacrylic acid of 50 to 90% by mass. (1-5) The carboxyl group derived from the methacrylic acid is neutralized by the first alkaline component and self-emulsifies in the aqueous medium, forming emulsion particles having a number average particle size of 30 to 300 nm.
2. 2. The overcoat material according to claim 1, wherein the first alkaline component is at least one selected from the group consisting of ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol.
3. 3. The overcoat material according to claim 1, further comprising a polymer (ii) that satisfies the following requirements (2-1) and (2-2): (2-1) At least one carboxyl group-containing polymer selected from the group consisting of polyethylene, polypropylene, poly-α-olefin, and copolymers thereof is neutralized with a second alkaline component and self-emulsified in the aqueous medium to form emulsion particles having a number average particle size of 30 to 300 nm. (2-2) The acid value of the polymer having a carboxy group is 10 to 150 mgKOH / g.
4. 4. The overcoat material according to claim 3, wherein the second alkaline component is at least one selected from the group consisting of ammonia, dimethylaminoethanol, and 2-amino-2-methyl-1-propanol.
5. The ultraviolet absorbing group-containing methacrylic acid monomer is 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole, 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-(2-ethylhexyloxy)-2-propyl methacryloyloxyethyl carbamate, 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)- The overcoat material according to any one of claims 1 to 4, which is at least one member selected from the group consisting of 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-dodecyloxy-2-propyl methacryloyloxyethyl carbamate and 1-[3-hydroxy-4-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]phenyloxy]-3-tridecyloxy-2-propyl methacryloyloxyethyl carbamate.
6. 6. The overcoat material according to claim 1, wherein the polymer (i) further contains 1 to 10% by mass of a structural unit derived from benzophenone methacrylate.
Citation Information
Patent Citations
Aqueous ink composition, recording using the same and recorded material recorded by using the same
JP1999199808A
Water-base ink composition, process for ink jet recording therewith, and recording recorded by using them
JP2000007967A
Inkjet recorded matter and manufacturing method therefor
JP2003276323A
Image forming method, image record, liquid composition and ink jet recording equipment
JP2004142446A
Method for inkjet recording and recorded article
JP2005052984A